Study on the Ablation Behavior of High-Intensity Lasers in Vacuum - Heyan Gao; Ying Wang; Jifei Ye; Bangdeng Du; Diankai Wang; Sai Li; Qianqian Cui; Sibo Wang; Tengfei Zhang (Applied Sciences)
Laser ablation has been extensively studied by researchers due to its high precision, high efficiency processing capabilities, and wide range of application potentials. However, in a vacuum environment, due to the complexity of experimental conditions, specific application scenarios, and interdisciplinary interferences, more in-depth research on the ablation behavior of high-intensity lasers in vacuum is still insufficient. In response to such issues, experiments were conducted on titanium alloy perforation using a nanosecond laser in a vacuum environment. The variations in ablation depth and volume as functions of pulse energy, pulse number, and defocus were investigated. Both the depth and volume ablation efficiencies were calculated, and the three-dimensional morphology of the ablation holes was captured. Additionally, the ablation plume was observed to support the research conclusions. The results indicate that within the number of high-intensity laser pulses, the ablation depth per pulse can be increased by more than four times, and the average ablation volume per pulse can reach 0.97 µm3/µJ. The enhanced sputtering of molten material during the multi-pulse laser ablation process in a vacuum environment is identified as the primary factor contributing to the increased ablation efficiency. With the advancement of science and technology and the growing demand for applications, this research is crucial for the further development of fields such as space exploration and technology, advanced manufacturing technology, and basic scientific research.